Epoxy coffee table with wood disc decoration / Muhammad Akmal Anuar - Anuar, Muhammad Akmal (Faculty of Applied Sciences, 2019)
Coffee table is a small low table usually placed in front of a sofa for holding bowls, magazines and others. Nowadays, people were use new raw material to create, coffee table such as epoxy resin which has some excellent characteristic that can be used in furniture production. In this study, the epoxy coffee table with wood disc decoration was designed and produced by using combination of wood disc from tree branches, epoxy resin and metal as the main raw material. The use of wood disc in this product was to reduce the waste from logging activities. After the product has been produced, the survey was done by distributing a set of online questionnaire through Google form application that involves 150 respondents including lectures, staff and students from Faculty of Applied Science UiTM Pahang campus Jengka. The issues have been analysed such as knowledge, raw material, design, marketing and satisfaction. Based on the result, most of the correspondents agreed about suitability of raw material, design of product, suitable price and the product can be commercialized in the market. Based on demographic analysis, there was indicated gender, profession, income and age. For the descriptive analysis results shows that the mean 4.34 for marketing variable was highest value for the rating score. Next, comparative analysis results show the gender indicated that male respondents get higher mean rating for marketing compared to female. For the profession, staff gave higher mean rating to all factors, the respondents who have income RM 1,000 to RM 3,000 give higher mean rate compared to others and lastly for age, from 50 years old and above give highest value mostly for all factors. Generally, based on correlation analysis shows the positive moderate correlation value for all factors included against customer satisfaction.